A comparative study of calf muscle circumference with other anthropometry measurement as a measure of low birth weight in neonates - Kumar, Siddharth; Jain, Hemant (International Journal of Contemporary Pediatrics, 2020)
Background: India having 3rd highest incidence of low birth weight (LBW) infants (28%) in the world. Majority of deliveries in our country are conducted at home by untrained traditional birth attendants or relatives, so it is not possible for untrained birth attenders to operate weighing machine in rural areas, therefore to find an alternative method for the estimation of low birth weight we used simple anthropometric indicators like calf circumference which is easily used by rural communities. Methods: It was a Cross-sectional study done at tertiary care center, Udaipur, Rajasthan, India during 1 year period in 2018. 150 neonates without any congenital malformation delivered at hospital irrespective of gestational age were subjected to anthropometric measurements. The different anthropometric measurements like calf circumference, chest circumference were used and data was analyzed by using Receiver Operating Characteristic curve (ROC) to find out the cut-off values with the highest sensitivity and specificity for birth weight <2500gm and <1800gm. For comparison Pearson's Correlation coefficients was used. Results: From different anthropometric measurements, calf circumference of 9.38 cm and 7.90cm had higher sensitivity and specificity in detecting birth weight babies of <2500gm, and <1800gm respectively. The best correlation was observed in calf circumference (r=0.989) and (r=0.990) for identifying babies with birth weight group 1.21-1.80kg and group 1.81-2.50kg. Conclusions: In the absence of a weighing machine, simple measurements like calf circumference is the best indicator in identifying low birth weight babies.